`(3x^2-7x-2)/(x^3-x)=(3x^2-7x-2)/[x(x+1)(x-1)]`

`(3x^2-7x-2)/(x^3-x)=A/x+B/(x+1)+C/(x-1)`

Multiply through by the LDC `x^3-x.`

`3x^2-7x-2=A(x^2-1)+Bx(x-1)+Cx(x+1)`

`3x^2-7x-2=Ax^2-A+Bx^2-Bx+Cx^2+Cx`

`3x^2-7x-2=(A+B+C)x^2+(-B+C)x-A`

Equate the coefficients of like terms. Then solve for A, B, and C.

`3=A+B+C`

`-7=-B+C`

`-2=-A`

`A=2`

`3=A+B+C`

`3=2+B+C`

`1=B+C`

Use the elimination method to solve for B and C.

`1=B+C`

`-7=-B+C`

_______________

`-6=2C`

`-3=C`

`1=B+C`

`1=B-3`

`4=B`

`A=2, B=4, C=-3`

`(3x^2-7x-2)/(x^3-x)=2/x+4/(x+1)-3/(x-1)`

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now